Penerimaan Inovasi Pembayaran Digital dalam Pelayanan Kesehatan - Jesika Zarasita Rambe; Rutiana Dwi Wahyunengseh; Asal Erlin Mulyadi (Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital technology has driven significant transformation in healthcare services, including in the aspect of service payment systems. Digital payment innovations, such as QR code-based cashless payments, digital wallets, and mobile banking, are seen as important components in realizing efficient, transparent, and patient-oriented healthcare services. This study aims to comprehensively examine the acceptance of digital payment innovations in healthcare services through a literature review approach. The results show that global healthcare services are moving towards a digital-first system that integrates telemedicine, electronic health records (EHR), artificial intelligence (AI), and digital payment systems into a single service ecosystem. Digital payments play an important role in improving administrative efficiency, speeding up transactions, and supporting the integration of clinical and financial services. The acceptance of digital payment innovations is influenced by ease of use, perceived benefits, trust and security, and supporting infrastructure conditions, especially in the aftermath of the COVID-19 pandemic. However, challenges such as cybersecurity risks, digital literacy gaps, and dependence on technological infrastructure remain barriers to implementation. Keywords: digital payments, healthcare services, digital health, innovation acceptance.